2010
DOI: 10.3109/09638281003797356
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of rehabilitation outcomes in day hospital and home settings for people with acquired brain injury – a systematic review

Abstract: The available studies indicate that outcomes of outpatient rehabilitation programmes delivered at home, of short-term duration (mostly 3 months) for people with stroke recently discharged from hospital, are at least equivalent to day hospital-based outpatient rehabilitation programme outcomes. However, there have been no controlled studies designed to investigate the influence of therapy context (home and clinic settings) on outcomes for people receiving outpatient neurological rehabilitation. Furthermore, inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 58 publications
0
37
0
3
Order By: Relevance
“…Those strategies included the same treating occupational therapist for each participant, a uniform treatment protocol, frequency and intensity across treatment settings and a uniform goal-planning and measurement approach with one independent assessor. These strategies were adopted in response to a systematic review of studies comparing outcomes of outpatient rehabilitation in home and day hospital settings, which noted that some studies were compromised by variations in intervention practices, treating therapists and teams and treatment intensity and amounts across comparison groups [23]. An alternative approach where a small sample size may only be practical and feasible with this population may be a single subject research design with multiple treatment and baseline phases to establish the effectiveness of interventions across settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Those strategies included the same treating occupational therapist for each participant, a uniform treatment protocol, frequency and intensity across treatment settings and a uniform goal-planning and measurement approach with one independent assessor. These strategies were adopted in response to a systematic review of studies comparing outcomes of outpatient rehabilitation in home and day hospital settings, which noted that some studies were compromised by variations in intervention practices, treating therapists and teams and treatment intensity and amounts across comparison groups [23]. An alternative approach where a small sample size may only be practical and feasible with this population may be a single subject research design with multiple treatment and baseline phases to establish the effectiveness of interventions across settings.…”
Section: Discussionmentioning
confidence: 99%
“…The authors conducted a systematic literature review to identify available evidence for the beneficial effect of therapy in the home setting over traditional day-hospital and outpatient clinic-based settings after inpatient rehabilitation for people with acquired brain injury (ABI) [23]. The review found no controlled studies comparing these two treatment settings for this population.…”
Section: Introductionmentioning
confidence: 99%
“…Home-based rehabilitation can be offered in different ways. The studies included in this review evaluated either ESD [5,6,9,10,20] and home-based rehabilitation (in most cases compared to none home-based rehabilitation) [21,22]. ESD aims to decrease the length of hospital stay after stroke and includes providing the client with support in the community setting after discharge.…”
Section: Selection Of Articlesmentioning
confidence: 98%
“…[85][86][87] Individual interviews with program personnel and data from the nominal groups with service users (people with IDD), and checklists of observation will be analyzed through qualitative thematic analysis. 88,89 First, an intra-case analysis will be done of the data for each case study.…”
Section: External Evaluation Of Programs For Social and Labor Inclusimentioning
confidence: 99%